A gestão das creches municipais de São Carlos na visão das diretoras: da assistência à educação (1999-2004) - Reis, Maria das Graças Fernandes de Amorim dos (2007)
This research refers to the management of early childhood education, representing a diagnosis of the early childhood education institutions in São Carlos, named Creches (Day Care Centers). This study is important because it intends to contribute to the discussion of some questions about children s education in Creches (Day Care Centers); moreover, due to the lack of exploitation of this theme. The research was focused on the configuration and specificities of early childhood education management in the Creches (Day Care Centers) once it was transferred from Social and Assisting Promotion Department to the Educational Department, defined by LDB Law number 9394/96. The study main target was to put in doubt the elements brought by the management to the discussion of the work in the Creches (Day Care Centers). The paper was organized in several parts, in order to cover methodological issues; early childhood education national policies and how they interact with the actions promoted by the city-hall; a description of the city Creches (Day Care Centers), mentioning some statistic data, organization and operation, professionals who work in the Creches (Day Care Centers) and the city actions to implement the early childhood education in the Creches (Day Care Centers) during the last four years (2001-2004); nowadays perspectives in school management, emphasizing the participative management and an analysis of the school administration/management under a foucaultian perspective, posing the area as a field of knowledge/power; the presentation and analysis of the data collected through interviews with São Carlos Creches (Day Care Centers) principals. To make this study possible, it was necessary to combine bibliographical research about the early childhood education matters, the school administration/management and the adopted references; the documents research meant to characterize the updated childhood education public policies, based on the laws, the plans and some others, like documents which read contents and prescriptions about the early childhood education; and the data collecting through 14 interviews testimonies with principals of the city Creches (Day Care Centers) in São Carlos. The results of these interviews were a great amount of data, from which we selected some speeches, the most important parts to help characterize the management, the discussion and the analysis suggested. In the closing, as final considerations, we reassured many points discussed throughout the paper, viewing the necessity to proceed a reflection about the possible precocious school process of young children, as long as the proposal of other studies about the management of the institutions that assist children from 0 to 3 years old.